Produção de etanol a partir de hidrolisado de bagaço de cana-de-açúcar utilizando Galactomyces geotrichum e Saccharomyces cerevisiae - Lamounier, Kênia Francisca Resende (2018)
The use of agroindustrial residues for the production of biofuels and other value-added products has been the subject of research in Brazil and in the world, being the sugarcane bagasse (SCB) one of the most studied by-products. In this context, the present work investigated the alkaline pre-treatment of SCB, followed by saccharification using commercial enzyme Cellic Ctec3 (under variable conditions of time and percentage of bagasse) and the alcoholic fermentation with commercial Saccharomyces cerevisiae and Galactomyces geotrichum UFVJM-R150 yeasts in the production of second generation ethanol (2G ethanol). The pre-treatment of the SCB with sodium hydroxide (NaOH 2%) was efficient for the removal of lignin, with a reduction of 58.15% in pre-treated bagasse (PTB). It was also observed that the cellulosic fraction was conserved and there was an increase of the porosity in the fibers in PTB. Concerning hemicelluloses, there was a removal of 31.66% in PTB. After saccharification, the concentrations of total reducing sugars (TRS) by the colorimetric method were quantified using 3.5 dinitrosalicylic acid (DNS) and the monosaccharides by high performance liquid chromatography (HPLC). The highest concentrations of TRS (73.96 g.L-1), and D-glucose and D-xylose (31.78 and 10.85 g.L-1, respectively) were obtained in the hydrolysate containing 10% PTB after 72 hours of hydrolysis. Then, alcoholic fermentations were performed, in which cell viability (CV) and ethanol production were evaluated. The greatest results were also obtained after the fermentations using the hydrolysate with 10% PTB (72 hours): G. geotrichum UFVJM-R150 with a peak of CV of 1.23x1010 cells.mL-1 and maximum ethanol production of 9.99 g.L-1(volumetric productivity - QP de 0,42 g.L-1.h-1 yield of ethanol as a function of the substrate - YP/S of 0.27 gethanol.gsugar-1) and S. cerevisiae with 7.76x 109 cells.mL-1 and 16.15 g.L-1of ethanol (QP of 0.67 g.L-1.h-1 and YP/S of 0.48 gethanol.gsugar-1). It was observed that, besides ethanol G. geotrichum UFVJM-R150 was able to produce other value-added products, such as galacturonic acid, propionic acid, isoamyl alcohol. These compounds were produced in different concentrations in the fermentations of hydrolysates 10% PTB (72 hours), YPX and model solution. The production of these secondary metabolites may enable the application of G. geotrichum UFVJM-R150 in biorefineries. In addition, the values of yield and productivity in ethanol and the consumption of D-glucose and D-xylose by G. geotrichum UFVJM-R150 were quite satisfactory. This is the first study which reports the 2G ethanol production and other byproducts by G. geotrichum UFVJM-R150 from PTB hydrolysates.